Growth and inequality convergence: The role of environmentally related impacts on human capital - Angela Cindy Emefa Mensah; Edward Barbier (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
We examine inequality convergence over the past three decades and ask if environmentally related impacts on health, and their effect on human capital, are responsible for the slow rate of inequality reduction in countries. Though higher initial incidence of environmentally related impacts on health simultaneously worsens the rate of inequality reduction, we find that those countries that experience faster reduction in the level of environmentally related impacts on health tend to converge to a lower level of inequality more quickly than their counterparts. Thus, estimates that exclude the incidence of environmentally related impacts on health may bias the speed of convergence downward. We conclude that high rates of income growth, per se, do not reduce inequality within developing countries. Instead, the level of both initial inequality and environmentally related impacts on health are just as important as growth. As such, policies targeted at reducing inequality must also address health impacts from the environment.
Keywords: D31; O15; Q51; Q52; 330; inequality; convergence; environmentally related impacts on health; income growth